The opinions of a multidisciplinary team in paediatric intensive care units regarding weaning protocols for mechanical ventilation - Njolomole, Abbie N (My University, 2015)
Background: Despite the empirical evidence of the significance of weaning protocols in Intensive Care Units, variations still exist in the adoption of weaning protocols. Multidisciplinary teams hold the responsibility for the introduction and development of weaning protocols in PICU. Purpose: To explore and describe the opinions of multidisciplinary teams practicing in the paediatric and cardiothoracic ICU at an academic hospital in Johannesburg concerning weaning protocols from mechanical ventilation. Design: Qualitative descriptive. Method: Data was collected from multidisciplinary team comprising of registered nurses (n=8) and doctors (n=2) practicing in PICU and CTICU who were purposively selected using semi-structured interviews to obtain qualitative information on their opinions regarding weaning protocols. Data collected was analysed using a Braun and Clarke method of qualitative thematic analysis. Seven categories were identified in which three themes, which provided the fundamental structure of the findings for the discussion, emerged and included the following:  Unstructured weaning – the current practice.  Recognition of the need for weaning protocols.  Being not in favour of weaning. Results: The majority of the multidisciplinary team members recognise the need to develop weaning protocols in PICU for standardisation of practice. Currently there are no weaning protocols and a multidisciplinary approach was identified as an important strategy to develop the protocols. However, nurses practicing in PICU are not trained in Critical Care nursing which poses a challenge to the practice. Conclusion This study indicates that there is need for the development of weaning protocols in PICU. Although nurses are weaning patients in PICU, there are no standardised weaning protocols to guide the practice. The study therefore suggests the need to develop weaning protocols through multidisciplinary approach and training of nurses in critical care nursing to improve knowledge base and skills. Keywords: Mechanical ventilation, weaning, protocols, paediatric patients, opinions/perception and multidisciplinary team.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2015
Keywords: Respiration, Artificial; Intensive Care Units, Pediatric